Knowledge towards Thalassemia and Willingness to Screen among Students in Public Senior High School 3 Bandung - Rima Destya Triatin; Lulu Eva Rakhmilia; Yunia Sribudiani; Susi Susanah (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Thalassemia carrier screening is a major preventive measure potentially influenced by the level of knowledge, particularly in adolescents. Therefore, this study aimed to analyze the effect of health education on knowledge of thalassemia in adolescents and its association with their willingness to do thalassemia screening.Methods: A cross-sectional study was conducted using data regarding knowledge of thalassemia before and after health education sessions from 229 students at Public Senior High-School 3 Bandung. All participants attended a one-day health education in July 2019. A questionnaire was filled in to measure their knowledge regarding thalassemia before and after the session, including knowledge on etiology and definition, risk of disease, clinical manifestations, treatment, complication, prognosis, and disease prevention. Only data with complete questionnaire responses were included. These responses were scored quantitatively and analyzed for their association with participants’ willingness to screen. Results: Participants were knowledgeable concerning thalassemia before the health education session (median, range: 60.0, 25.0-90.0), and knowledge was increased significantly after the education session (median, range: 80.0, 35.0-100.0) with an increased median difference=19.99 (p-value <0.001). Although there was no significant association between the overall post-test score on participants’ willingness to screen (p-value >0.05), the willingness was slightly associated with improved knowledge regarding the risk of disease (OR: 1.02; 95%CI: 1.00-1.03; p-value <0.005). Conclusion: Health education regarding thalassemia significantly increases general knowledge of thalassemia. However, improving knowledge is not significant in influencing adolescents’ motivation to take the screening tests.